Design and Simulation of PMSM Feedback Linearization Control System - SONG Xiao-jing (Institute of Advanced Engineering and Science, 2013)
With the theory of AC adjustable speed as well as a new control theory research is unceasingly thorough, the permanent magnet synchronous motor control system requires high precision of control and high reliability of the occasion, access to a wide range of applications, in the modern AC motor has play a decisive role position. Based on the deep research on the feedback linearization technique based on, by choosing appropriate state transformation and control transform, PMSM model input output linearization, and the design of the feedback linearization controller, realized PMSM decoupling control based on Matlab, and PMSM feedback linearization control system simulation. The simulation results show that, the system in a certain range of speed than the traditional PI controller has better control performance, but to the parameter variation has strong sensitivity. It also determines the direction for future research. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2192